2007
DOI: 10.1083/jcb.200707010
|View full text |Cite
|
Sign up to set email alerts
|

Stress-dependent relocalization of translationally primed mRNPs to cytoplasmic granules that are kinetically and spatially distinct from P-bodies

Abstract: Cytoplasmic RNA granules serve key functions in the control of messenger RNA (mRNA) fate in eukaryotic cells. For instance, in yeast, severe stress induces mRNA relocalization to sites of degradation or storage called processing bodies (P-bodies). In this study, we show that the translation repression associated with glucose starvation causes the key translational mediators of mRNA recognition, eIF4E, eIF4G, and Pab1p, to resediment away from ribosomal fractions. These mediators then accumulate in P-bodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
294
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(316 citation statements)
references
References 37 publications
15
294
2
1
Order By: Relevance
“…In contrast, at 37°, and to a lesser extent at 34°, rat8-2p and mex67-5p appear unable to terminate their association with mRNA, and REGs form when these mRNAs are released from polysomes. Hoyle et al (2007) also observed a class of mRNP-containing granules distinct from P-bodies that formed after glucose deprivation and contained, in addition to mRNA, eIF4E, eIF4G1, and Pab1p.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, at 37°, and to a lesser extent at 34°, rat8-2p and mex67-5p appear unable to terminate their association with mRNA, and REGs form when these mRNAs are released from polysomes. Hoyle et al (2007) also observed a class of mRNP-containing granules distinct from P-bodies that formed after glucose deprivation and contained, in addition to mRNA, eIF4E, eIF4G1, and Pab1p.…”
Section: Discussionmentioning
confidence: 79%
“…The fate of translationally repressed mRNAs following glucose depletion has also been analyzed. mRNAs enter cytoplasmic foci termed P bodies or stress granules or are degraded (Hoyle et al 2007;Buchan et al 2008;Arribere et al 2011). P bodies and stress granules form with different kinetics and contain different protein components (Hoyle et al 2007;Buchan et al 2008) and repressed mRNAs enter P bodies at different times after stress .…”
Section: Global Approaches To Studying Translation Controlsmentioning
confidence: 99%
“…mRNAs enter cytoplasmic foci termed P bodies or stress granules or are degraded (Hoyle et al 2007;Buchan et al 2008;Arribere et al 2011). P bodies and stress granules form with different kinetics and contain different protein components (Hoyle et al 2007;Buchan et al 2008) and repressed mRNAs enter P bodies at different times after stress . After several hours of starvation, growth resumes with a distinct pattern of highly translated mRNAs, allowing enhanced synthesis of mitochondrial-targeted proteins (Vaidyanathan et al 2014).…”
Section: Global Approaches To Studying Translation Controlsmentioning
confidence: 99%
“…[11][12][13] Third, mRNP granules exhibit dynamic interactions with one another such as docking, fusion, or apparent maturation from one granule type to the next. Examples include P-body-stress granule docking, fusion 11,14 and apparent maturation, 11,12 P-body-neuronal transport granule docking, 15 P-granule-P-body docking 16 and nuage-P-body fusion, and apparent maturation into sponge bodies. 16,17 The simplest interpretation of such observations is that mRNPs are exchanged between different granules, though this has not been directly demonstrated, 13 and remains an important unresolved issue.…”
Section: Diversity and Similarity Among Different Mrnp Granule Typesmentioning
confidence: 99%
“…Thus, mRNA decay blocks could also affect germ granules and neuronal transport granules, with which P-bodies also physically interact. 14,15 Notably, various mRNA degradative enzymes are found in mRNP granules besides P-bodies, such as Xrn1 in stress granules 11 and Drosophila/mouse spermatid nuage, 65 Dcp1/ Dcp2 in various germ granules, [66][67][68] and several Argonaute proteins with endonuclease activity in stress granules, 69 and various germ granules. [70][71][72][73] Whether mRNA degradation occurs in mRNP granules besides P-bodies remains poorly studied.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%